Pituitary Neoplasm Nomenclature Workshop: Does Adenoma Stand the Test of Time? - Ho, Ken; Fleseriu, Maria; Kaiser, Ursula; Salvatori, Roberto; Brue, Thierry; Lopes, M. Beatriz; Kunz, Pamela; Molitch, Mark; Camper, Sally A.; Gadelha, Monica; Syro, Luis; Laws, Edward; et al. (Journal of the Endocrine Society, 2021)
The WHO Classification of Endocrine Tumours designates pituitary neoplasms as adenomas. A proposed nomenclature change to pituitary neuroendocrine tumors (PitNETs) has been met with concern by some stakeholder groups. The Pituitary Society coordinated the Pituitary Neoplasm Nomenclature (PANOMEN) workshop to address the topic. Experts in pituitary developmental biology, pathology, neurosurgery, endocrinology, and oncology, including representatives nominated by the Endocrine Society, European Society of Endocrinology, European Neuroendocrine Association, Growth Hormone Research Society, and International Society of Pituitary Surgeons. Clinical epidemiology, disease phenotype, management, and prognosis of pituitary adenomas differ from that of most NETs. The vast majority of pituitary adenomas are benign and do not adversely impact life expectancy. A nomenclature change to PitNET does not address the main challenge of prognostic prediction, assigns an uncertain malignancy designation to benign pituitary adenomas, and may adversely affect patients. Due to pandemic restrictions, the workshop was conducted virtually, with audiovisual lectures and written precis on each topic provided to all participants. Feedback was collated and summarized by Content Chairs and discussed during a virtual writing meeting moderated by Session Chairs, which yielded an evidence-based draft document sent to all participants for review and approval. There is not yet a case for adopting the PitNET nomenclature. The PANOMEN Workshop recommends that the term adenoma be retained and that the topic be revisited as new evidence on pituitary neoplasm biology emerges.
CRIS-Team WoS Importer:2021-05-28